Grinding hardened steel using MQL associated with cleaning system and cBN wheel - Javaroni, Rafael Liberatti [UNESP]; Lopes, Jose Claudio [UNESP]; Garcia, Mateus Vinicius [UNESP]; Ribeiro, Fernando Sabino Fonteque; Sanchez, Luiz Eduardo de Angelo [UNESP]; Mello, Hamilton Jose de [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
The minimum quantity lubrication (MQL) is one of the most promising alternative techniques to replace the conventional application of cutting fluids. However, its use in grinding is still a challenge, as overheating and wheel clogging occur, leading to workpiece quality worsening. This work investigates a wheel cleaning jet associated with the MQL (MQL+WCJ) at three flow rates in grinding of AISI 4340 hardened steel with a cBN wheel, comparing the results with MQL and conventional methods. The output parameters assessed were workpiece surface roughness, roundness deviation, and microhardness, diametrical wheel wear, acoustic emission, and grinding power, and the machined surfaces were analyzed through microscopy techniques (optical, scanning electron, and confocal). The MQL+WCJ outperformed MQL in all the tested conditions. The application of the wheel cleaning jet reduced by up to 73% the wheel wear, 69% the surface roughness, 45% the roundness deviation, 60% the acoustic emission, and 24% the grinding power, regarding MQL without wheel cleaning, contributing to a more environmentally friendly and efficient grinding.
Keywords: Grinding; Minimum quantity lubrication; Wheel cleaning jet; Surface integrity